Curcumin alleviates OGD/R-induced PC12 cell damage via repressing CCL3 and inactivating TLR4/MyD88/MAPK/NF-κB to suppress inflammation and apoptosis. (21st May 2020) - Wang, Chao; Yang, Yong-Hong; Zhou, Liang; Ding, Xin-Li; Meng, Ying-Chun; Han, Ke
Abstract: Objectives: Curcumin presents some therapeutic effects including anti-cancer and anti-inflammation. Herein, we centred on the functional role of curcumin in cerebral ischaemia injury and its potential molecular mechanisms. Methods: Microarray analysis was used for excavating crucial genes in cerebral ischaemia. PC12 cells were subjected to oxygen–glucose deprivation and reoxygenation (OGD/R) to imitate cerebral ischaemia/reperfusion (I/R) injury in vitro . Cell viability and apoptosis abilities were evaluated by Cell Counting Kit-8 and flow cytometry assays. qRT-PCR, Western blot and enzyme-linked immunosorbent assays were performed to assess the concentrations of related genes. Key findings: By enquiring GEO dataset, C–C motif chemokine ligand 3 (CCL3) was profoundly upregulated in cerebral I/R injury model. And CCL3 was found to be highly expressed in PC12 cells suffered from OGD/R. Moreover, we found that CCL3 was a potential target of curcumin in cerebral I/R injury. More importantly, the following experiments illustrated that curcumin inhibited the expression of CCL3 in OGD/R model and reduced cell apoptosis and inflammation. Moreover, high expression levels of TLR4, MyD88, p-NF-κB P65, p-P38 MAPK and p-IκBα in OGD/R model were inhibited by curcumin. Conclusions: Our study manifested that curcumin might be a meritorious drug for the treatment of cerebral ischaemia by acting on CCL3.